2000
DOI: 10.1021/jm9903848
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MK-944a:  A Second Clinical Candidate from the Hydroxylaminepentanamide Isostere Series of HIV Protease Inhibitors

Abstract: Recent results from human clinical trials have established the critical role of HIV protease inhibitors in the treatment of acquired immune-deficiency syndrome (AIDS). However, the emergence of viral resistance, demanding treatment protocols, and adverse side effects have exposed the urgent need for a second generation of HIV protease inhibitors. The continued exploration of our hydroxylaminepentanamide (HAPA) transition-state isostere series of HIV protease inhibitors, which initially resulted in the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The use of these molecules has been associated with a drastic reduction in AIDS morbidity and mortality, mainly with the introduction of several HIV protease inhibitors on the therapeutic intervention of AIDS (Palella et al, 2003;Fear et al 2007;Tan et al, 2010;Wensing et al, 2010). Currently, there are nine protease inhibitors in clinical use: saquinavir, ritonavir, indinavir, nelfinavir, amprenavir, lopinavir, atazanavir, darunavir e tipranavir (Roberts et al, 1990;Dorsey et al, 1994;Kim et al, 1995;Kaldor et al 1997;Sham et al, 1998;Turner et al, 1998;Robinson et al, 2000;Brower et al, 2008; Figure 3). These inhibitors present low oral bioavailability and short plasma half-life (Barry et al 1997;Bouzide et al, 2005, Castro et al, 2006.…”
Section: A Recent Aspartyl Family Member: Hiv Proteasementioning
confidence: 99%
See 1 more Smart Citation
“…The use of these molecules has been associated with a drastic reduction in AIDS morbidity and mortality, mainly with the introduction of several HIV protease inhibitors on the therapeutic intervention of AIDS (Palella et al, 2003;Fear et al 2007;Tan et al, 2010;Wensing et al, 2010). Currently, there are nine protease inhibitors in clinical use: saquinavir, ritonavir, indinavir, nelfinavir, amprenavir, lopinavir, atazanavir, darunavir e tipranavir (Roberts et al, 1990;Dorsey et al, 1994;Kim et al, 1995;Kaldor et al 1997;Sham et al, 1998;Turner et al, 1998;Robinson et al, 2000;Brower et al, 2008; Figure 3). These inhibitors present low oral bioavailability and short plasma half-life (Barry et al 1997;Bouzide et al, 2005, Castro et al, 2006.…”
Section: A Recent Aspartyl Family Member: Hiv Proteasementioning
confidence: 99%
“…Currently, there are eight protease inhibitors in clinical use: (a) ritonavir (Brower et al, 2008); (b) saquinavir (Roberts et al, 1990); (c) nelfinavir (Kaldor et al, 1997); (d) indinavir (Dorsey et al, 1994); (e) amprenavir (Kim et al, 1995); (f ) atazanavir (Robinson et al, 2000); (g) lopinavir (Sham et al, 1998); and (h) tipranavir, one protease inhibitor currently under development (Turner et al, 1998; Figure 3).…”
Section: A Recent Aspartyl Family Member: Hiv Proteasementioning
confidence: 99%
“…Since the existing PIs target the active site of HIV protease and have similar structures, most of the drug-resistant HIV proteases confer cross-resistance to multiple PIs. There is a great need for second-generation PIs with different chemical structures and/or with an alternative mode of inhibition [8,9]. In addition, reduced general toxicity may be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some natural herbal substances have been shown to be effective at inhibiting the growth of HIV in vitro at different stages in HIV-1 replication [10,11]. Collins et al [8] reported that 6 out of 19 aqueous herbal extracts significantly inhibited the interaction between HIV-1 gp120 and immobilized CD4 receptors. Several extracts have also been shown to be capable of inhibiting the activity of recombinant HIV-1 protease [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Wilkerson et al synthesized and evaluated a series of nonsymmetrically substituted cyclic ureacarboxamides (S8) for the inhibition of HIV-proteases [13]. Dorsey et al presented the 3-pyridylmethyl-hydroxylaminpentenamides (S9) as a clinical backup of the most widely prescribed HIV protease inhibitor called indinavir [14]. Various structure and shape based attempts to design novel HIV protease inhibitors have been appeared in the literature [15].…”
Section: Introductionmentioning
confidence: 99%